2013
DOI: 10.1093/gbe/evs134
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Makeup of the Marine Flavobacterium Nonlabens (Donghaeana) dokdonensis and Identification of a Novel Class of Rhodopsins

Abstract: Rhodopsin-containing marine microbes such as those in the class Flavobacteriia play a pivotal role in the biogeochemical cycle of the euphotic zone (Fuhrman JA, Schwalbach MS, Stingl U. 2008. Proteorhodopsins: an array of physiological roles? Nat Rev Microbiol. 6:488–494). Deciphering the genome information of flavobacteria and accessing the diversity and ecological impact of microbial rhodopsins are important in understanding and preserving the global ecosystems. The genome sequence of the orange-pigmented ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 77 publications
(94 reference statements)
0
70
0
Order By: Relevance
“…In nonmarine aquatic environments, 35 to 62% of genomes within metagenomic assemblies harbor a rhodopsin (14), while analysis of freshwater bacterioplankton metagenomic assemblies and single amplified genomes from the same locations suggested the presence of a rhodopsin in 37 to 56% and 8 to 20% of the samples, respectively (35). These studies have demonstrated that rhodopsins are both more abundant and more diverse than previously suspected (10,(36)(37)(38). However, metagenomic and metatranscriptomic data cannot demonstrate that a rhodopsin is functional, nor can they consistently identify the organism that hosts the rhodopsin.…”
mentioning
confidence: 54%
“…In nonmarine aquatic environments, 35 to 62% of genomes within metagenomic assemblies harbor a rhodopsin (14), while analysis of freshwater bacterioplankton metagenomic assemblies and single amplified genomes from the same locations suggested the presence of a rhodopsin in 37 to 56% and 8 to 20% of the samples, respectively (35). These studies have demonstrated that rhodopsins are both more abundant and more diverse than previously suspected (10,(36)(37)(38). However, metagenomic and metatranscriptomic data cannot demonstrate that a rhodopsin is functional, nor can they consistently identify the organism that hosts the rhodopsin.…”
mentioning
confidence: 54%
“…In contrast, a light-driven proton pump KR1 grows slowly, suggesting different functional roles other than generation of membrane potential. After submission of this paper, one paper was reported in which the presence of a light-driven sodium ion pump was proposed based on an enhanced expression of a marine bacterium at high salt concentration 45 . The present results are fully consistent with their proposal, and a light-driven sodium ion pump is now experimentally proven.…”
Section: Article Nature Communications | Doi: 101038/ncomms2689mentioning
confidence: 99%
“…2), one containing rhodopsins pumping sodium and another containing rhodopsins pumping chloride. The sodium pumps have been found in Bacteroidetes, as well as in members of the Deinococcus-Thermus phylum isolated from very different environments (40,87,88). Interestingly, sodium pumps have been shown to have dual functionality, transporting protons and halogens depending on the chemical environment (40,50,89).…”
Section: Phylogenetic Distribution Of Microbial Rhodopsins According mentioning
confidence: 99%